B-cell antigen receptor activates transcription factors NFAT (nuclear factor of activated T-cells) and NF-κB (nuclear factor κB) via a mechanism that involves diacylglycerol. (1st February 2004) - Antony, P.; Petro, J.B.; Carlesso, G.; Shinners, N.P.; Lowe, J.; Khan, W.N.
Abstract : Engagement of the B-cell antigen receptor (BCR) induces the activation of various transcription factors, including NFAT (nuclear factor of activated T-cells) and NF-κB (nuclear factor κB), which participate in long-term biological responses such as proliferation, survival and differentiation of B-lymphocytes. We addressed the biochemical basis of this process using the DT40 chicken B-cell lymphoma. We discovered that Bruton's tyrosine kinase (BTK) and phospholipase C-γ2 (PLC-γ2) are required to activate NFAT and NF-κB, and to produce the lipid second messenger diacylglycerol in response to BCR cross-linking. Therefore the functional integrity of the BTK/PLC-γ2/diacylglycerol signalling axis is crucial for BCR-directed activation of both transcription factors NFAT and NF-κB.